The Inheritance Pattern of Geculan Bocah Dance in Tanon Hamlet, Ngrawan Village, Getasan Sub-District, Semarang Regency - Anindya Syafa'at Nur Isnaeni; Wiyoso, Joko (Universitas Negeri Semarang, 2024)
The people of Tanon Hamlet have developed folk arts, one of which is the Geculan Bocah Dance. Geculan Bocah dance is a manifestation of a children's game. This dance is developed and maintained through a process of inheritance. Inheritance pattern is an activity that has the purpose of maintaining and developing an art object from time to time to keep it alive in the development of the times. The purpose of the study is to describe the inheritance pattern and performance form of the Geculan Bocah dance in Tanon Hamlet. The method used in the research is a descriptive qualitative method, using sociology and ethnocoreology approaches. Data collection used observation, interview, and documentation techniques. Data analysis was conducted using data collection techniques, data reduction, data presentation, and conclusion. The data validity test used triangulation techniques. The results show that the inheritance pattern of Geculan Bocah dance in Tanon Hamlet adheres to three inheritance pattern systems namely